2014
DOI: 10.2174/1871527313666140612102841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Anxiety and Depression Disorders: Review of Meta- Analyses and Neurobiological Mechanisms

Abstract: Anxiety and depression are the most frequently diagnosed psychological diseases showing a high co-morbidity. They have a severe impact on the lives of the persons concerned. Many meta-analytical studies suggested a positive anxiolytic and depression-reducing effect of exercise programs. The aim of the present article is to synthesize metaanalyses on the effects of exercise on anxiety and depression and to describe average effect sizes. For this purpose 37 meta-analyses were included reporting 50 effect sizes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
242
3
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(287 citation statements)
references
References 0 publications
18
242
3
24
Order By: Relevance
“…While regular physical activity/exercise has been shown to improve depression and anxiety symptoms, 26 approximately 50% of those diagnosed with these disorders in our study did not exercise re gularly (i.e. at least once a week), highlighting an opportunity for improvement in the care and management of such individuals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…While regular physical activity/exercise has been shown to improve depression and anxiety symptoms, 26 approximately 50% of those diagnosed with these disorders in our study did not exercise re gularly (i.e. at least once a week), highlighting an opportunity for improvement in the care and management of such individuals.…”
Section: Discussionmentioning
confidence: 65%
“…[17][18][19][20][21] A limited number of studies on the effects of exercise as a treatment strategy for anxiety disorders have shown generally positive effects of exercise, 19,22 but the impact (effect size) is usually smaller than that observed for depressive symptoms. 26 There is a lack of data describing individuals who engage in or conversely who do not engage in physical activity/exercise to help manage their mood and/or anxiety disorders. This is the first study in Canada to examine the uptake of this strategy in a nationally representative sample of people with mood and/or anxiety disorders living in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the neurobiological mechanisms of physical activity are suggested to be similar to those of antidepressants (Wegner et al, 2014). Physical activity has also been reported to have many other health benefits over traditional treatments (Josefsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…L'activité physique et l'exercice comme traitement donnent de meilleurs résultats, dans le cas de dépression bénigne ou légère, que les interventions de contrôle, et des résultats parfois comparables à ceux des thérapies classiques (médicaments ou TAO) 1721 . Quelques études sur les effets de l'exercice comme stratégie de traitement des troubles d'anxiété en ont démontré les bienfaits 19,22 , mais son impact (l'ampleur de son effet) est habituellement plus modeste que celui observé dans le cas de symptômes de dépression 26 .…”
Section: Introductionunclassified